2020
DOI: 10.1302/1863-2548.14.200105
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tourniquet use in paediatric lower leg surgery

Abstract: Background The purpose of this study is to evaluate the use of the tourniquet and its effect on post-operative pain in the paediatric population following lower leg procedures. Methods A retrospective study of paediatric patients (under the age of 18) undergoing inpatient orthopaedic procedure below the knee performed at a single academic institution between 1st December 2013 and 31st January 2019 was conducted. Primary outcome measures of total opioid consumption during hospital stay and pre-operative nerve b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…This is an example of a tourniquet associated adverse event that is entirely preventable through the correct application of a shut-off. Similar to the evidence from the adult population ( 16 ), tourniquet use is associated with increased post-operative pain and analgesia ( 62 ), which can prolong hospital stay and interfere with rehabilitation.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…This is an example of a tourniquet associated adverse event that is entirely preventable through the correct application of a shut-off. Similar to the evidence from the adult population ( 16 ), tourniquet use is associated with increased post-operative pain and analgesia ( 62 ), which can prolong hospital stay and interfere with rehabilitation.…”
Section: Discussionmentioning
confidence: 71%
“…Hanna et al included 204 children who underwent lower limb orthopaedic surgery. Tourniquet use was associated with increased pain levels and post-operative analgesia requirements ( 62 ). Mean tourniquet time was 75.9 min (range: 7–195), but tourniquet pressures were not reported.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the present study, patients tended to have a higher complication rate and pain after implantation of hemiepiphysiodesis plates at higher tourniquet pressures. Accordingly, Hanna et al [ 22 ] found a reduction of opioid consumption in the postoperative period by avoiding the use of tourniquet in pediatric patients with lower limb surgery. Another study from Kamath et al [ 23 ] found that the incidence of tourniquet pain was directly proportional to the duration of tourniquet use but not to the amplitude of tourniquet inflation pressure.…”
Section: Discussionmentioning
confidence: 99%